Propithecus verreauxi demography spanning 40 years at Bezà Mahafaly Special Reserve, southwest Madagascar - Joelisoa Ratsirarson; Jeannin Ranaivonasy; Richard Lawler; Isabella Fiorentino; Nelson Rios; Alison Richard (Scientific Data)
Abstract The diverse, highly endemic flora and fauna of Madagascar make it a priority for research and conservation. Lemurs, the island’s endemic primates, exhibit a distinctive array of biological, behavioral and demographic traits. Research on these species contributes to significant theoretical issues, including the evolution of mammalian life histories and social systems. Virtually all 107 extant lemur species are threatened with extinction or critically endangered, and a better understanding of demography and the drivers of demographic change is needed to inform management strategies for surviving wild populations. Sifaka (Propithecus verreauxi) have been continuously studied and demographic parameters have been monitored at the Bezà Mahafaly Special Reserve in southwest Madagascar since 1984. We have compiled a dataset encompassing over 900 individuals that have been tagged and followed during this period, and new data continue to be added. Data provide information on male and female life history parameters, individual development and aging, and social group dynamics. The dataset is an important resource for both research and management.